Impasse; Fearing Duty-Free; Anna Bayle [videorecording] - Lazaro, Cheche (The Probe Team, 1994)
Summary: Deals with the issue on Total Log Ban bill; the Duty-Free Philippines competing with other department stores; and the exclusive interview of most successful ramp model, Anna Bayle.